Sustainable development in a center-periphery model - Gabriel Porcile (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
Latin American Structuralism is an important strain in development theory, one which focuses on the center-periphery dynamics arising from an international economy ridden by technological, financial and power asymmetries. This paper discusses recent Structuralist contributions around the concept of sustainable development, defined as a growth path that is sustainable in three dimensions: economic, social and environmental. The economic dimension of sustainability means that the effective rate of growth is compatible with the Balance-of-Payments constraint; the social dimension means that growth is inclusive and reduces inequality; and the environmental dimension means that it respects the ecological boundaries of the planet. There are no endogenous market forces that could deliver a sustainable growth path: the role of politics and political negotiations (at the domestic and international levels) is paramount. The effective path that will be observed emerges as political power and structural change co-evolve and create tensions and disequilibria, shaping income distribution and the direction of industrial transformation and technological change.
Keywords: O11; O43; O44; 330; Center-periphery models; Structuralism; sustainable development